2002
DOI: 10.2741/penber
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish as a model for human disease

Abstract: Much of our current understanding of the function of genes modulating the normal process of embryonic development has come from mutant analysis. The availability of thousands of mutant lines in zebrafish that allows for identification of novel genes regulating various aspects of embryogenesis has been instrumental in establishing zebrafish as a robust and reliable genetic system. With the advances in genomic sequencing, the construction of several genetic maps, and cloning of hundreds of ESTs, positional cloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 144 publications
0
44
0
1
Order By: Relevance
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) has been demonstrated as an excellent genetic model for studying vertebrate development and diseases (Penberthy et al, 2002). In addition, the availability to establish green fluorescent protein (GFP) transgenic lines under tissuespecific promoters further aid the study of morphogenetic process during development (Kawakami, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish are gaining increasing popularity as a valuable model of human diseases because their organs and genetics are similar to those of humans 1,2 . In the field of developmental biology, many studies have demonstrated that zebrafish and human show marked similarity in hematopoiesis 3 , hemostasis 4,5 , and myelopoiesis 6 .…”
Section: Introductionmentioning
confidence: 99%